Literasi Digital: Pondasi Kesiapan Sumber Daya Manusia Untuk Indonesia Emas 2045 - Akhmad Aris Tantowi; Hanggono Arie Prabowo; Siti Alifah (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Indonesia is currently facing significant challenges in preparing Human Resources (HR) to achieve the vision of Golden Indonesia 2045, especially in the context of a demographic bonus that is expected to be an opportunity but also has the potential to become a disaster if not anticipated well. This research aims to explore the role of digital literacy as a foundation in preparing competent and high-quality human resources to face these challenges. The method used is a descriptive qualitative approach, with a sample of 12 high school students in Bekasi Regency. Data collection was conducted through documentation, in-depth interviews, and observations to explore information about students' digital literacy skills and their views on the importance of these skills for the future. The research results indicate that students possess basic skills in using information technology, although their knowledge of more complex tools and applications is still limited. Students actively use digital learning resources, but there is variation in their ability to assess the quality of these resources. The majority of students recognize the importance of digital literacy and believe that these skills will impact their career and educational opportunities in the future. This research concludes that the development of digital literacy needs to focus not only on technical aspects but also on ethics and responsibility in using technology. Therefore, suggestions to enhance digital literacy competencies among students are essential to support the achievement of the Indonesia Emas 2045 vision, so that future generations can compete and contribute positively on the global stage.